Household Demand For Fruits And Vegetables In Malaysia - K Subramaniam, Mangaleswari (2022)
In Malaysia, the globalisation process has driven the country to experience changes in food consumption patterns. Amidst the changing diversification of food consumption patterns, several challenges also arise in the Malaysian Fruits and Vegetables (FV) industries. This study estimates FV’s own-price, cross-price, income demand elasticity and evaluates nutrient demand elasticities using Malaysia Household Expenditure Survey (MHES) data set 2014. Demand is forecasted to predetermine the FV demand from 2025–2040. To achieve these objectives, the Quadratic Almost Ideal Demand System (QUAIDS) model is used. This study involved two categories of fruits: non-seasonal and seasonal, and three categories of vegetables: root, leafy and fruity vegetables.